Study of Biopharmaceutical Properties and Stability of "Enformin" and "Sitmet" Tablets - .M. Yunusova, Kh; B. Ilkhamova, N.; Tashmatova, M.A.; Muslimaxon Jamshid Qizi, Anvarova (Journal of Neonatal Surgery, 2025)
One of the biopharmaceutical studies assessing the therapeutic effect of drugs is their biological efficacy. One of the main methods for evaluating the biopharmaceutical properties of drugs in in vitro experiments is the "Rotating Basket" method, which is included in the State Pharmacopoeia of the Republic of Uzbekistan. It is known from the literature that the release rate of the active substance is influenced by various factors, including the excipients used, the volume and pH of the solvent medium, and the basket rotation speed